Barriers to Outpatient Pediatric Chronic Pain Clinic Participation Among Referred Patients. (September 2020) - Boppana, Sushmitha S.; Miller, Rebecca; Wrona, Aubrey; Tumin, Dmitry; Wrona, Sharon; Smith, Timothy P.; Bhalla, Tarun; Kim, Stephani S.; Tobias, Joseph D.
Initial clinic evaluation among referred patients and factors limiting treatment initiation are not well characterized. We conducted a retrospective review of referrals to our outpatient pain clinic to identify intake visits and factors associated with treatment initiation among adolescents with chronic pain. We identified adolescents aged 13 to 18 years at the time of referral to clinic (2010-2016). Factors associated with completion of visits were evaluated using logistic regression. Patients who completed visits more frequently had private insurance than public or no insurance ( P = .053). The most common reasons for caregiver decision not to attend the pain clinic included use of another pain clinic, that services were not wanted or no longer needed, and that their child was undergoing further testing. The current study demonstrated that patients with head pain were more likely to complete an intake visit, while there was a trend showing that lack of private insurance decreased this likelihood.